Energy Tax and the Downstream Palm Oil Trade Competitiveness Nexus in Malaysia: An Application of GMM Approach - Othman, Norashida; Yusop, Zulkornain; Ismail, Mohd Mansor; Afandi, Syamsul Herman Mohammad (International Journal of Energy Economics and Policy, 2021)
This paper analyses the impact of energy tax imposed in European Union countries on Malaysia’s downstream palm oil trade competitiveness. The competitiveness factors consist four major attributes adopted from Porter Diamond Model (PDM) framework introduced by Porter (1990) that determine the national competitiveness and analyses using the dynamic generalized method of moments (GMM) proposed by Arellano and Bond (1991). The study utilizes yearly data spanning from 2009 until 2016. The results indicate that energy taxes have positive and significant influence on Malaysia’s trade competitiveness of palm oil downstream products (oleochemicals, biodiesel and palm-based finished products) and the result also suggests that all the main factors of PDM (i.e factor condition; demand condition; firm strategy and rivalry; and related supporting industry) significantly influence the competitiveness of the industry. The policy recommendation remains that, in order for Malaysia to improve the competitiveness of palm oil downstream industries, producers need to ensure that the country’s palm oil production is sustainable, which is stipulated by international agreements, especially in EU countries, where environmental sustainability is their main concern. Keywords: Competitiveness, Palm Oil Downstream, Energy tax, Porter Hypothesis, DGMM JEL Classifications: A11, Q02, R11 DOI: https://doi.org/10.32479/ijeep.11558